2020
DOI: 10.1371/journal.pone.0238938
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with stillbirth in selected countries of South Asia: A systematic review of observational studies

Abstract: Background Despite having the high rate of stillbirth in most of the countries of South Asia, there is a lack of synthesized evidence based on factors associated with stillbirth. This study systematically synthesizes the evidence on factors associated with stillbirth in the four selected countries of South Asia. Methods This review was conducted using Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) guidelines. Studies that examined factors as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
16
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 38 publications
6
16
1
Order By: Relevance
“…[6][7][8] Additionally, 57% and 50.7% of stillbirths were observed in primiparous mothers in some studies. [16][17][18][19] The percentage of primiparous mothers with stillbirths in the present study is very close to some other studies. [19][20][21] In our study, 60.3% of stillborn babies were preterm.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…[6][7][8] Additionally, 57% and 50.7% of stillbirths were observed in primiparous mothers in some studies. [16][17][18][19] The percentage of primiparous mothers with stillbirths in the present study is very close to some other studies. [19][20][21] In our study, 60.3% of stillborn babies were preterm.…”
Section: Discussionsupporting
confidence: 87%
“…[13][14][15] Compared to available studies on stillbirth, the incidence of stillbirth found in this study is possibly the highest compared to other South Asian countries. 16 It is found that stillbirth is more common among mothers aged 20-25 years (43.65%) in this study. Nearly 70% of stillbirths occurred among mothers aged between 20-35 years.…”
Section: Discussionmentioning
confidence: 48%
“…Evidence suggests that the prevalence of adverse pregnancy outcomes such as preeclampsia, C-section delivery, macrosomia, low birthweight, still births and IUGR is high in South Asian countries. [15][16][17][18] For example, Poudel et al (2020) 17 reported that the pooled stillbirth rate in India, Bangladesh, Nepal and Pakistan was 25.15 per 1,000 births. Another study reported that, the prevalence of C-section delivery is around 13% in South Asian countries.…”
Section: Introductionmentioning
confidence: 99%
“…The time of birth is considered to be extremely crucial for both mother and the child as the chances of complication is high during this stage [10]. Su cient literary evidence supports the prevalence of high-risk pregnancy and pre-term birth among the Indian and other south Asian population [11][12][13][14][15]. Therefore, the delivery of the baby crucially requires an appropriate setting, where lifesaving equipment is available and hygienic conditions are fully maintained.…”
Section: Introductionmentioning
confidence: 99%